2018
DOI: 10.1002/jcp.27481
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene attenuates oxidative stress and preserves mitochondrial function in astrocytic cells upon glucose deprivation

Abstract: Oxidative stress and mitochondrial dysfunction induced by metabolic insults are both hallmarks of various neurological disorders, whereby neuronal cells are severely affected by decreased glucose supply to the brain. Likely injured, astrocytes are important for neuronal homeostasis and therapeutic strategies should be directed towards improving astrocytic functions to improve brain's outcome. In the present study, we aimed to assess the actions of raloxifene, a selective estrogen receptor modulator in astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…As maintenance of neuronal homeostasis is an important function of astrocytes, to enhance astrocytic functions in this respect would present promising therapeutic strategies for improvement of brain function otherwise impaired by injury and disease. Encouragingly, it was found in cell culture that application of 1 µM raloxifene as a pretreatment to glucose-deprivation of astrocytic cells results in increases in cell viability and attenuation of nuclei fragmentation [ 57 ]. These favorable effects are associated with raloxifene reduction of oxidative stress and preservation of mitochondrial function [ 57 ].…”
Section: Brain Cell Types and The Effects Of Raloxifenementioning
confidence: 99%
See 3 more Smart Citations
“…As maintenance of neuronal homeostasis is an important function of astrocytes, to enhance astrocytic functions in this respect would present promising therapeutic strategies for improvement of brain function otherwise impaired by injury and disease. Encouragingly, it was found in cell culture that application of 1 µM raloxifene as a pretreatment to glucose-deprivation of astrocytic cells results in increases in cell viability and attenuation of nuclei fragmentation [ 57 ]. These favorable effects are associated with raloxifene reduction of oxidative stress and preservation of mitochondrial function [ 57 ].…”
Section: Brain Cell Types and The Effects Of Raloxifenementioning
confidence: 99%
“…Encouragingly, it was found in cell culture that application of 1 µM raloxifene as a pretreatment to glucose-deprivation of astrocytic cells results in increases in cell viability and attenuation of nuclei fragmentation [ 57 ]. These favorable effects are associated with raloxifene reduction of oxidative stress and preservation of mitochondrial function [ 57 ]. These results also suggested direct effects of raloxifene on mitochondria [ 57 ].…”
Section: Brain Cell Types and The Effects Of Raloxifenementioning
confidence: 99%
See 2 more Smart Citations
“…In inflammatory in vitro and in vivo models, it has been shown that administration of oestradiol and selective ER modulators (SERMs) decreases the expression of the pro‐inflammatory cytokines IL‐1β, IL‐10 and TNFα . Raloxifene, another SERM, has also been shown to protect mitochondria in astrocytic cells exposed to glucose deprivation . By contrast, administration of oestradiol can modulate the mitogenic stimulation of B and T lymphocytes and, as a consequence, increase the production of immunoglobulins such as immunoglobulin M. Indeed, epidemiological studies have shown that women of any age experience lower rates of infection and mortality associated with inflammatory processes compared to men …”
Section: Oestrogens and The Brainmentioning
confidence: 99%